Determining the stability of accuracy of genomic estimated breeding values in future generations in commercial pig populations. (17th March 2021) - Hollifield, Mary Kate; Lourenco, Daniela; Bermann, Matias; Howard, Jeremy T; Misztal, Ignacy
Abstract: Genomic information has a limited dimensionality (number of independent chromosome segments [M e ]) related to the effective population size. Under the additive model, the persistence of genomic accuracies over generations should be high when the nongenomic information (pedigree and phenotypes) is equivalent to Me animals with high accuracy. The objective of this study was to evaluate the decay in accuracy over time and to compare the magnitude of decay with varying quantities of data and with traits of low and moderate heritability. The dataset included 161, 897 phenotypic records for a growth trait (GT ) and 27, 669 phenotypic records for a fitness trait (FT ) related to prolificacy in a population with dimensionality around 5, 000. The pedigree included 404, 979 animals from 2008 to 2020, of which 55, 118 were genotyped. Two single-trait models were used with all ancestral data and sliding subsets of 3-, 2-, and 1-generation intervals. Single-step genomic best linear unbiased prediction (ssGBLUP ) was used to compute genomic estimated breeding values (GEBV ). Estimated accuracies were calculated by the linear regression (LR ) method. The validation population consisted of single generations succeeding the training population and continued forward for all generations available. The average accuracy for the first generation after training with all ancestral data was 0.69 and 0.46 for GT and FT, respectively. The average decay in accuracy from the first generation after training to generation 9 was −0.13 and −0.19 for GT and FT, respectively. The persistence of accuracy improves with more data. Old data have a limited impact on the predictions for young animals for a trait with a large amount of information but a bigger impact for a trait with less information.